2021
DOI: 10.3390/foods10061321
|View full text |Cite
|
Sign up to set email alerts
|

Applying Pulsed Electric Fields to Whole Carrots Enhances the Bioaccessibility of Carotenoid and Phenolic Compounds in Derived Products

Abstract: We propose the application of pulsed electric fields (PEF) to carrots to obtain derived products with increased phenolic and carotenoid bioaccessibility. For this purpose, juices, purees, and oil-added purees were obtained from whole PEF-treated carrots (five pulses of 3.5 kV cm−1; 0.61 kJ kg−1). In order to obtain shelf-stable products, the effect of a thermal treatment (70 °C for 10 min) was also studied. Carrot juices exhibited the highest carotenoid (43.4 mg/100 g fresh weight) and phenolic (322 mg kg−1 dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 69 publications
0
13
0
Order By: Relevance
“…Thus, it can damage the host tissue. 10,19 Second, it can decrease local secretion of pro-inflammatory mediators by modulating the key transcription factors. 10,20 Lastly, it can decrease free radicals production.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it can damage the host tissue. 10,19 Second, it can decrease local secretion of pro-inflammatory mediators by modulating the key transcription factors. 10,20 Lastly, it can decrease free radicals production.…”
Section: Discussionmentioning
confidence: 99%
“…8 The most dominant phenolic compound in carrots is chlorogenic acid which can reduce the release of inflammatory mediators, especially TNF-α. 9,10 Carrots also contain flavonoids that inhibit acid secretion, reduce pepsin level and activity, and also increase gastric mucous and bicarbonate secretion. Flavonoids also have antioxidative, anti-inflammatory, and cytoprotective effect.…”
Section: Introductionmentioning
confidence: 99%
“…Due to its high hydrophobicity, β-carotene is extracted using organic solvents such as hexane, acetone, methanol and ethanol, as well as various solvent combinations [11]. Efficient and sustainable approaches have also been developed for β-carotene extraction, based on the application of pulsed electric fields [28], microwaves [29,30], ultrasounds [31], supercritical fluids [32,33] and pressurized liquids [34,35]. β-carotene was also extracted from carrot peel waste by a green procedure without any solvent, based on water-induced hydrocolloidal complexation with pectin [36].…”
Section: Technologies For β-Carotene Encapsulation In Dried Systemsmentioning
confidence: 99%
“…Indeed, fast freezing rate produces small ice crystals. The ice crystal size affects heat and mass transfer properties during dehydration as well as porosity and rehydration of the dried product [28]. The sublimation process is strongly affected by pressure, which determines the ice sublimation temperature.…”
Section: Technologies For β-Carotene Encapsulation In Dried Systemsmentioning
confidence: 99%
“…In vitro studies have been performed to obtain insights on the bioaccessibility of fat-soluble vitamins and provitamins, i.e., their release from the lipid phase of the food matrix and solubilization within the mixed micelles formed from lipid digestion products, which is the process governing their bioavailability [13,14]. Through in vitro digestion studies, it was found that the bioaccessibility of β-carotene in raw carrot puree is very low (3.8%), and it increases only moderately after thermal treatments of oil-added purees (10.7%) [15]. To optimize the use of β-carotene, an approach is the extraction of this compound from food sources, such as carrots, and then its encapsulation into specific nano-or micro-structures that enable its homogeneous distribution in the food matrix and improve its bioaccessibility [14].…”
Section: Introductionmentioning
confidence: 99%